Some reflections from the past and some ideas for the future: The 2014 Kempe Oration. (May 2015) - Oates, Kim
Abstract: Although the physical features of child abuse had been described before 1962, it was Henry Kempe et al.'s article "The Battered Child Syndrome" that is regarded as the beginning of widespread awareness and acceptance of this previously hidden problem. It was another 15 years before child sex abuse started to receive similar widespread recognition. As awareness of child abuse increased, its size became apparent. Funds were poured into child abuse detection and Child Protective Services, although evaluation of the effects of these initiatives did not proceed at the same pace. In those early days, child abuse was conceived in pathological terms, as a problem found only in particular types of families. We now know it is more helpful to use an ecological model and in so doing to consider societal, community, family, and individual factors in interaction. As for the future, we have much to learn from areas such as: public health, where a preventive approach is emphasized; the interaction between researchers and front line workers and insights from high reliability organizations that have been so beneficial to the patient safety movement. In particular, new research about the way our environment and our experiences can influence the way our genes function may reveal new opportunities for prevention, early intervention, and treatment.